Analysis of Water Governance on Declaration Construction for Water Supply Resilience for Dry Land Agriculture (Study in Kupang District, NTT Province) - Emilia GIE; David Wilfrid RIHI; Thomas W.A. ISLIKO; Rouwland Alberto BENYAMIN; William Febrianus Umbu IBIRUNI; Wita Nuriyani NDUN (PT Keberlanjutan Strategis Indonesia, 2025)
Air availability has a very close influence on supporting food security. Air is an important input for agricultural production. Due to the dependence on water, during the dry season, many rivers and streams dry up and to overcome this community problem, the Kupang Regency government built a reservoir as a water reserve medium for. As one of the agricultural barns in NTT Province, it is necessary to conduct an analysis of water governance in the construction of reservoirs for the resilience of air supply for dry land agriculture in Kupang Regency, NTT Province. The method used in this study is a descriptive method with a qualitative approach with a total of 76 people who were determined purposively, then the primary and secondary data collected were analyzed using data analysis techniques from Creswell (2016). The results of the study found that water governance in the construction of reservoirs for air supply resilience for agriculture in Kupang Regency uses the theory of Van der Kerk, et al. (2013:8) with research results on aspects, 1) Uneven information flow, lack of training, and poor strategies hinder water use; 2) No clear roles between institutions, private sectors, and communities in management; 3) Policymakers are not involved in decision-making for water management processes.